2013
DOI: 10.4049/jimmunol.1200947
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Production by Amyloid β–Specific Th1 Cells Promotes Microglial Activation and Increases Plaque Burden in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by the presence of amyloid-β (Aβ)–containing plaques, neurofibrillary tangles, and neuronal loss in the brain. Inflammatory changes, typified by activated microglia, particularly adjacent to Aβ plaques, are also a characteristic of the disease, but it is unclear whether these contribute to the pathogenesis of AD or are a consequence of the progressive neurodegenerative processes. Furthermore, the factors that drive the inflammation and neurodegeneration remain poorly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
193
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(206 citation statements)
references
References 66 publications
8
193
4
1
Order By: Relevance
“…Another inflammatory cytokine that apparently aggravates AD is IFN-γ, i.e. Aβ-specific CD4+ Th1 cells adoptively transferred to an AD mouse model increased microglia activation and Aβ deposition, effects that were attenuated with an IFN-γ antibody (27). Yet, this study showed that while Th2 cells had beneficial effects, the Th17 cells did not cause damage, despite being strongly inflammatory.…”
Section: Rev Neuropsiquiatr 78 (3) 2015contrasting
confidence: 44%
“…Another inflammatory cytokine that apparently aggravates AD is IFN-γ, i.e. Aβ-specific CD4+ Th1 cells adoptively transferred to an AD mouse model increased microglia activation and Aβ deposition, effects that were attenuated with an IFN-γ antibody (27). Yet, this study showed that while Th2 cells had beneficial effects, the Th17 cells did not cause damage, despite being strongly inflammatory.…”
Section: Rev Neuropsiquiatr 78 (3) 2015contrasting
confidence: 44%
“…Further, the stimulation of Ab-reactive T cells at sites of Ab plaques resulted in IFNc-induced chemotaxis of leukocytes and therapeutic clearance of Ab (Fisher et al 2010). In contrast, recent data indicate that IFN-c produced by T-cells infiltrating the brain in AD tend to elevate microglial activation, Ab deposition and impaired cognitive functions, and these effects were ameliorated by systemic administration of anti-IFN-c antibody in mice with AD (Browne et al 2013).…”
Section: Microglia In Ad Brainsmentioning
confidence: 89%
“…To evaluate the impact of MCC950 in a model of AD, APP/PS1 mice were treated for 3 months from 12 months, an age at which cognitive changes are evident (Browne et al, 2013) and Aβ plaques are well developed. We show that MCC950 attenuated the genotype-related deficits in 2 tests of cognition, and that this was accompanied by a reduction in Aβ plaque numbers and soluble Aβ concentration reflecting the ability of MCC950 to increase phagocytosis of Aβ.…”
Section: Discussionmentioning
confidence: 99%